2021
DOI: 10.1177/0960327121991901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenofibrate on proliferation of SMMC-7721 cells via regulating cell cycle

Abstract: Liver cancer is a malignant cancer with great harmfulness. Fenofibrate is a peroxisome proliferation activated receptor (PPARα) agonist widely used in the treatment of dyslipidemia. Previous studies have shown that fenofibrate may promote cell proliferation, but the underlying mechanism has not been fully characterized. The aim of this study was to investigate the role of PPARα agonist fenofibrate in cell proliferation of SMMC-7721 cells compared with that of THLE-2 cells. SMMC-7721 and THLE-2 cells were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Tauber and colleagues reported stimulation of the proliferation of MCF-7 breast cancer cells with low fibrate concentrations, and suppression with high doses [ 45 ]. Dose-dependent effects of fibrates on cell proliferation have also been reported for human liver cancer cells [ 46 ]. The sustained activation of PPARα leads to liver tumorigenesis in rodents.…”
Section: Ppars and Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tauber and colleagues reported stimulation of the proliferation of MCF-7 breast cancer cells with low fibrate concentrations, and suppression with high doses [ 45 ]. Dose-dependent effects of fibrates on cell proliferation have also been reported for human liver cancer cells [ 46 ]. The sustained activation of PPARα leads to liver tumorigenesis in rodents.…”
Section: Ppars and Cell Proliferationmentioning
confidence: 99%
“…In contrast, the induction of apoptosis in hepatocellular carcinoma cells via the overexpression of PPARα was dependent on NF-κB signaling, as PPARα was found to directly interact with IκBα (nuclear factor kappa-light-polypeptide-gene-enhancer in B-cells inhibitor alpha) [ 52 ]. In contrast to most studies suggesting a pro-apoptotic function of PPARα activation, Li and coworkers reported that the PPARα inhibitor MT886 induced apoptosis in hepatocarcinoma cell lines, and the agonist fenofibrate significantly increased proliferation, the expression of cell-cycle-related protein (CyclinD1, CDK2), and cell-proliferation-related proteins (PCNA) [ 46 ]. Similarly, Abu Aboud and colleagues demonstrated enhanced apoptosis in renal-cell carcinoma upon PPARα inhibition in vitro [ 193 ] and in vivo through a decrease in enhanced fatty-acid oxidation and oxidative phosphorylation, and further cancer-cell-specific glycolysis inhibition [ 194 ].…”
Section: Ppars and Cell Deathmentioning
confidence: 99%
“…SMMC-7721 cells (1 × 10 5 ) were seeded into a 6-cm Petri dish for 24 h and treated with IC 50 of compounds 5-8 for 24 h, and then, cells were harvested and fixed with pre-cooled 70% ethanol and stored at -20 ℃ overnight. The fixed cells were washed with PBS and re-suspended with PBS containing PI (50 μg/mL; Sigma) and RNase A (100 μg/mL; Sigma) at 4 ℃ for 30 min (Li et al 2021).…”
Section: Determination Of Reactive Oxygen Species (Ros) Productionmentioning
confidence: 99%
“…Stain, an HMG-CoA reductase inhibitor which exerts significant effects in lowering cholesterin (TC) and low-density lipoprotein (LDL) levels, was found to exhibit protective effects against CRC by reducing the dilatation activity and enhancing the chemotherapeutic sensitivity of CRC cells ( Bardou et al, 2010 ). In addition, studies have demonstrated the anti-tumor effects of fibrates, which function mainly in reducing LDL and triglyceride (TG) levels, against CRC and other digestive neoplasms ( Chen et al, 2020 ; Kong et al, 2021 ; Li et al, 2021 ). Cholesterol accumulation, which exceeded the ability of liver conversion and intestinal absorption, was reported as high risk factor of CRC ( Waluga et al, 2018 ; Gu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%